Effectiveness 2 Years Postexit of a Recently Established Mental Health Court. (February 2013) - Burns, Padraic J.; Hiday, Virginia Aldigé; Ray, Bradley
There are now more than 300 mental health courts in the United States; yet studies on their effectiveness in reducing criminal recidivism are relatively few, and most follow defendants after entry into the court, during their participation, and sometimes, for a short period following exit. Using a preenrollment-postexit design that follows participants of one mental health court for 2 years after exit, this article examines criminal recidivism of participants after they no longer receive the court's services, supervision, and support. It investigates participant demographic, clinical, and criminal history and key arrest characteristics as well as process measures and graduation as predictors of two measures of recidivism, arrests, and postexit jail days. Its findings support the hypothesis that mental health courts can reduce criminal recidivism postexit and point to criminal history, time in mental health court, and graduation as the main influences on recidivism.